Underground interiors : decorating for alternate life styles - Skurka, Norma; Gili, Oberto (New York : Quadrangle Books, Inc., 1972)
This book is an exploration into the revolt against old concepts of decor and old ways of living - a look at the new living environments closely linked to recent developments in art, politics, and the press, all of which have taken the name "underground" to distinguish them from their establishments counterpart.
Introduction -- Surrealist interiors -- Environments -- Radical chic -- Pop culture -- Space age habitations.
Keywords: INTERIOR DESIGN -- FURNISHINGS